Direct human DNA protection by Coriolus versicolor (Yunzhi) extract. (July 2013) - Szeto, Yim Tong; Lau, Po Chun; Kalle, Wouter; Pak, Sok Cheon
Abstract Context and objective: Scientific evidence has shown Coriolus versicolor (L. ex Fr.) Quel (also known as Yunzhi) has the role of immunomodulator in therapeutic effect. The aim of this in vitro study was to investigate the antioxidative effect of Yunzhi and to explore the mechanisms behind its DNA protection. Materials and methods: Commercial Yunzhi extract was dissolved in water and diluted in five concentrations (101–105 μg/L) with appropriate buffers. Lymphocytes harvested from three healthy subjects were incubated with Yunzhi extract for 30 min. Cells were then subjected to 5 min oxidant challenge by 45 μM hydrogen peroxide. The standard alkaline comet (SAC) assay and lysed cell comet (LCC) assay were performed in parallel. DNA damage of each treatment was scored under a fluorescence microscope and compared with the cells without Yunzhi pretreatment. Results: U-shaped dose–response was seen in both versions of the comet assay. Yunzhi at 104 μg/L demonstrated a genoprotective effect against oxidative damage in the SAC assay (25% decrease in comet score). In the LCC assay, a trend of protection in lymphocytes was observed but it did not reach statistical significance. Conclusion: A direct antioxidant effect of Yunzhi against oxidant challenge on the DNA of lymphocytes was evidenced. The active component in Yunzhi was likely to be membrane permeable.